Does Separating Intentionality From Mental Representation Imply Radical Enactivism? - Schlicht, Tobias (Frontiers in Psychology, 2018)
Traditionally, intentionality is regarded as that feature of all and only mental states – paradigmatically beliefs and desires – in virtue of which they are directed at or are about something. The problem of intentionality is to explain how it fits into the natural order given the intuition that no physical entity can be intentionally directed in this sense. The basic assumption of this paper, proposed by enactivists, is that failure to naturalize intentionality and mental representation is partly due to the fact that most participants in the debate take intentionality and mental representation to be equivalent. In contrast, it is proposed to treat intentionality as a feature of whole embodied agents (paradigmatically organisms) who can be directed at objects and states of affairs in various ways, while representation should be regarded as a feature of mental states (and their respective vehicles or underlying mechanisms). The present paper develops and motivates the distinction, applies it to Metzinger’s project of naturalizing phenomenal representation, and demonstrates the range of theoretical options with respect to a delineation of cognition given the enactive proposal. It is taken as problematic that enactivism takes the realm of cognition to be identical to the realm of biology. Instead, a constraint on a theory of intentionality and representation is that it should delineate the subject matter of cognitive science and distinguish it from other sciences, also to leave room for the possibility of artificial intelligence. One important implication of the present proposal is that there can be creatures which can be intentionally directed without having the capacity to represent. That is, their intentionality is restricted to being able to be directed at existent things. Only creatures in possession of the right kind of neurocognitive architecture can produce and sustain representations in order to be directed at non-existent things. It is sketched how this approach conceives of intentionality as a developmental and layered concept, allowing for a hierarchical model of varieties of intentionality, ranging from the basic pursuit of local environmental goals to thoughts about fictional objects.